2020
DOI: 10.1111/1759-7714.13426
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation treatment of durvalumab after chemoradiation in real‐world patients with stage III unresectable non‐small cell lung cancer

Abstract: Background: Treatment for stage III non-small cell lung cancer (NSCLC) of unresectable disease mainly involves concurrent chemoradiation (CRT). Post-CRT consolidation treatment with durvalumab is a major therapeutic advance that provides survival benefit in this group of patients. However, the performance of this treatment strategy remains to be studied in a real-world setting. Methods: A total of 31 patients who had disease control post-CRT were included in the durvalumab early access program (EAP) as an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
7
26
1
Order By: Relevance
“…Pneumonitis (15%, 4 patients) was the predominant toxicity resulting in treatment interruption. All these findings are in close accordance with recently published data [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…Pneumonitis (15%, 4 patients) was the predominant toxicity resulting in treatment interruption. All these findings are in close accordance with recently published data [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…AEs were defined using the National Cancer Institute‐Common Terminology Criteria for Adverse Events (NCI‐CTCAE), version 4.0. One study used the NCI‐CTCAE, version 5.0 31 and another used the NCI‐CTCAE, version 3.0 7 . The included studies primarily reported the total AE rates and immune‐related or radiation pneumonitis rates associated with combination therapy using PD‐1/PD‐L1 inhibitors and RT.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of pooled data from 66 prospective trials of ICIs (which included 25,836 patients) showed that the incidence of hematological toxicity and pneumonitis associated with combined radio‐immunotherapy may be slightly higher than that of RT alone, whereas the incidence of colitis, hepatitis, and myocarditis may be slightly lower, although these differences were statistically nonsignificant. We observed that some of the included single‐arm studies reported a relatively high incidence of AEs or mild pneumonitis 29,31,33,36 . The method of administration of combined radio‐immunotherapy 33 and the small sample size of some of the included studies (which is likely to have introduced a risk of bias) could have contributed to these results.…”
Section: Discussionmentioning
confidence: 96%
“…A Japanese retrospective analysis of 108 patients found that rates of grade 1, 2, and 3 pneumonitis were 58%, 26%, and 1% with a V20 constraint of 35% 23 . Another analysis of 31 patients found that pneumonitis occurred in 17.2% of all patients, and was of at least grade 3 in 6.9% of these patients 24 . In Table 4 we have summarized the incidence of pneumonitis associated with ICI consolidation therapy in Asian patients in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another analysis of 31 patients found that pneumonitis occurred in 17.2% of all patients, and was of at least grade 3 in 6.9% of these patients. 24 In Table 4 we have summarized the incidence of pneumonitis associated with ICI consolidation therapy in Asian patients in different studies. These analyses indicate that the pneumonitis rates range from 17.2% to 85% (pooled rate: 67.1%), with grade 3 or higher pneumonitis occurring in 0%-14.3% of patients (pooled rate: 4.4%, Table 4).…”
Section: Discussionmentioning
confidence: 99%